LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING SYMBOLIC TERHADAP KEMATANGAN KARIER SISWA DI SMP NEGERI 14 CIMAHI - Silvi Kirana Fatmala; Agus Hasbi Noor; Maya Masyita Suherman (IKIP Siliwangi, 2026)
This study aims to determine whether the symbolic modeling technique can improve students’ career maturity in group counseling services. Career maturity refers to an individual’s readiness to plan and make career decisions appropriately according to their developmental stage. The research was conducted at SMP Negeri 14 Cimahi. The method used was a mixed-method approach with an Explanatory Sequential Design. The subjects were 8 eighth-grade students selected through purposive sampling, based on the criterion of having low career maturity scores. Data were collected through both test instruments questionnaires and non-test instruments interviews and observations. The results showed that the average score before the service was 74.88, and after the service, it increased to 115.5, indicating a significant improvement. Furthermore, the t-test analysis using SPSS 25.0 revealed a significance value (2-tailed) of 0.000, which is less than 0.05. Therefore, it can be concluded that the symbolic modeling technique is effective in improving students’ career maturity.